2004
DOI: 10.1016/j.virol.2003.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA polymerase scanning and the gymnastics of Sendai virus RNA synthesis

Abstract: mRNA synthesis from nonsegmented negative-strand RNA virus (NNV) genomes is unique in tht the genome RNA is embedded in an N protein assembly (the nucleocapsid) and the viral RNA polymerase does not dissociate from the template after release of each mRNA, but rather scans the genome RNA for the next gene-start site. A revised model for NNV RNA synthesis is presented, in which RNA polymerase scanning plays a prominent role. Polymerase scanning of the template is known to occur as the viral transcriptase negotia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 81 publications
2
93
0
Order By: Relevance
“…On the other hand, SeV (83) and Henipavirus would provide examples of the second scenario, with K D values in the M range. These findings would support a cartwheeling mechanism for the polymerase complex of Henipavirus, as already proposed for other Paramyxoviridae members (132,133). Whatever the mechanism by which the polymerase moves along the template, the present studies, by revealing that P is recruited onto the nucleocapsid template via the N TAIL -P XD interaction, designate this latter as a promising target for antiviral therapies.…”
Section: Structural Models Of Henipavirus N Tail -P Xd Complexes and supporting
confidence: 86%
“…On the other hand, SeV (83) and Henipavirus would provide examples of the second scenario, with K D values in the M range. These findings would support a cartwheeling mechanism for the polymerase complex of Henipavirus, as already proposed for other Paramyxoviridae members (132,133). Whatever the mechanism by which the polymerase moves along the template, the present studies, by revealing that P is recruited onto the nucleocapsid template via the N TAIL -P XD interaction, designate this latter as a promising target for antiviral therapies.…”
Section: Structural Models Of Henipavirus N Tail -P Xd Complexes and supporting
confidence: 86%
“…SeV genomes contain six major proteins: NP, P, M, F, HN, and L expressed in a gradient with NP having the highest level of expression (40). Cells were infected with equal MOIs of SeV-52 or SeV-C for 3, 6, or 24 h. Quantitative analysis of mRNA extracted from these cells revealed that, at all time points, the cells infected with SeV-52 produced more viral NP mRNA than cells infected with SeV-C (Fig.…”
Section: Sev-c Produces More Activating Stimulus Than Sev-52mentioning
confidence: 99%
“…This general model of polymerase organization has resulted from numerous studies on measles and closely related viruses (reviewed in Refs. [1][2][3][4][5][6]. The purpose of this note is to address a specific disagreement in the literature concerning the regions of measles N involved in binding the feet of the polymerase.…”
Section: Introductionmentioning
confidence: 99%